Annual faculty recognition awards - De La Salle University, Manila (Animo Repository, 2003)
One hundred twenty four faculty members were recognized for their accomplishments in strengthening DLSU's reputation as a world-class educational institution during the Annual Faculty Recognition Awards. Highlighted in the program were the giving of 37 faculty medals and 79 service medal awards.